PENCAPAIAN TARGET NASIONAL PADA BIDANG ADMINISTRASI KEPENDUDUKAN DI DINAS KEPENDUDUKAN DAN PENCATATAN SIPIL KOTA TIDORE KEPULAUAN - indramayu; Wiwik Roso Sri Rejeki; imelda hutasoit (Institut Pemerintahan Dalam Negeri, 2025)
Abstract The Directorate General of Population and Civil Registration of the Ministry of Home Affairs has set performance achievement targets for 2024 for the Population and Civil Registration Offices at the regency/city level, as outlined in the Minister of Home Affairs Decree Number 100.4.6-635 Dukcapil of 2024. Accordingly, the Population and Civil Registration Offices are implementing various efforts and strategies to improve performance targets that are still relatively low, namely electronic ID card (KTP-el) recording (92.24%), Child Identity Card (KIA) ownership (33.32%), and the implementation of Digital Population Identity (IKD) (8.9%). However, these efforts and strategies have not been fully effective due to several obstacles, such as geographical conditions, limited telecommunications infrastructure, budget constraints, and shortages of KTP-el blanks. This research focuses on strategies to enhance the achievement of national targets, aiming to identify and analyze existing obstacles through SWOT analysis. This research is descriptive qualitative, with informants selected using purposive and snowball sampling techniques. Data analysis was conducted using qualitative methods, including organizing and preparing data for analysis, reading all data, coding data, identifying themes, developing interpretations, further analysis using analytical frameworks, and presenting and interpreting the research findings. The results indicate that, based on the SWOT analysis, achieving the performance targets requires extensive socialization efforts through social media platforms such as TikTok, Instagram, Facebook, and others. It is also necessary to establish collaborations with related agencies and user institutions to optimize the utilization of population data and documents. Keywords: Performance Target, SWOT Analysis, Population Documents